Improving the Process and Learning Outcomes of Pancasila Education through the Discovery Learning Model in Grade III of Elementary School - Saviny Alqorama Ayda; Abdullah Abdullah; Megawati Megawati (Jurnal Inovasi Pendidikan dan Sains, 2025)
This classroom action research was conducted at SDN 91/VI Rantau Panjang VI. The objective of the study was to improve the learning process and outcomes of Pancasila Education in Grade III through the implementation of the Discovery Learning model. The research was carried out in two cycles, each consisting of two meetings. Data were collected using teacher and student observation sheets and student achievement tests. The results showed significant improvement in both teaching performance and student engagement. In the first cycle, the teacher’s observation score increased from 64.70% (Fair) in the first meeting to 76.47% (Good) in the second. In the second cycle, the scores rose to 82.35% and then to 94.11% (Very Good). Student activity also increased from 57.14% (Poor) to 71.42% (Fair) in the first cycle, and further improved to 92.85% (Very Good) in the second cycle. Learning outcomes improved as well, with only 9 students (64.28%) achieving mastery in the first cycle, increasing to 13 students (92.85%) in the second. These findings confirm that the Discovery Learning model effectively enhances both the learning process and outcomes in Pancasila Education and is recommended as an alternative instructional strategy.